2010
DOI: 10.1007/s00401-010-0760-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Creutzfeldt–Jakob disease and fatal familial insomnia: insights into phenotypic variability and disease pathogenesis

Abstract: Human prion diseases are a group of rare neurodegenerative disorders characterized by the conversion of the constitutively expressed prion protein, PrP(C), into an abnormally aggregated isoform, called PrP(Sc). While most people who develop a prion disease have no identifiable cause and a few acquire the disease through an identified source of infection, about 10-15% of patients are affected by a genetic form and carry either a point mutation or an insertion of octapeptide repeats in the prion protein gene. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 160 publications
3
108
0
4
Order By: Relevance
“…5,6 At present, descriptions of patients with the D178N/Met129 PRNP phenotype are few. 7 We report a patient with the D178N/Met129 PRNP mutation, affected by FFI without typical refractory insomnia early in the disease course or MRI changes in the thalamus.…”
Section: Introductionmentioning
confidence: 92%
“…5,6 At present, descriptions of patients with the D178N/Met129 PRNP phenotype are few. 7 We report a patient with the D178N/Met129 PRNP mutation, affected by FFI without typical refractory insomnia early in the disease course or MRI changes in the thalamus.…”
Section: Introductionmentioning
confidence: 92%
“…The N terminus of PrP is also clearly involved in familial and transmissible prion diseases. Additional octapeptide repeats are observed in familial human PrP diseases (33), and mice lacking the N-terminal amino acids 32-93 and 23-31 are less susceptible to transmissible prion diseases (34,35). Furthermore, the N terminus of PrP has been associated with numerous cellular features such as lipid rafts (36), RNA binding (37), micropinocytosis (38), and neuroprotection (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Note that codon 129 encodes for two amino acids, methionine (M) and valine (V). A phenotypic influence in inherited prion diseases associated with codon 129 has been investigated and summarized in (Kovacs et al, 2002;Capellari et al, 2011). Regarding to second characteristic, Paramithiotis et al showed that the Tyr-Tyr-Arg motif in PrP, which is a hydrophilic-like fragment, will be exposed to solvent when PrPC is converted into PrPSc.…”
Section: Diagnosismentioning
confidence: 99%